2022
DOI: 10.1155/2022/1563352
|View full text |Cite|
|
Sign up to set email alerts
|

English Education Tutoring Teaching System Based on MOOC

Abstract: In the process of continuous reform and development of education and teaching, some traditional teaching modes are gradually eliminated, whereas new teaching modes are gradually recognized by teachers and students. These modes are widely used in education and teaching due to their overwhelming characteristics. Among these emerging teaching modes, massive open online course (MOOC) is a relatively advanced teaching mode with a better application effect. Quickly and accurately detecting the cheating behavior of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…The results of the study provide empirical evidence supporting the advantages of MOOCs in the context of General Education courses, as students reported finding them beneficial for their studies. These findings are consistent with prior research conducted by Alyoussef (2021), Ji and Cao (2016), Mi (2022), Nath et al (2014), andTsai et al (2018), which also highlight the positive impacts of MOOCs in educational settings. The suitability of MOOCs for undergraduate education is evident, as they cater to the diverse learning styles of students, offering a flexible and adaptable learning environment that accommodates individual preferences.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results of the study provide empirical evidence supporting the advantages of MOOCs in the context of General Education courses, as students reported finding them beneficial for their studies. These findings are consistent with prior research conducted by Alyoussef (2021), Ji and Cao (2016), Mi (2022), Nath et al (2014), andTsai et al (2018), which also highlight the positive impacts of MOOCs in educational settings. The suitability of MOOCs for undergraduate education is evident, as they cater to the diverse learning styles of students, offering a flexible and adaptable learning environment that accommodates individual preferences.…”
Section: Discussionsupporting
confidence: 92%
“…Scholars have extensively explored the benefits and potential applications of Massive Open Online Courses (MOOCs) in education (Alyoussef, 2021;Ji & Cao, 2016;Mi, 2022;Nath et al, 2014;Tsai et al, 2018). Alyoussef (2021) focuses on the significance of Task-Technology Fit (TTF) in the acceptance of MOOCs for promoting sustainability in higher education.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mi [24] has developed a hybrid approach for MOOC cheating detection based on deep learning. By including CNN, the model significantly enhances the detection performance of a single model.…”
Section: Methodsmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%